Mergers and acquisitions : a guide to creating value for stakeholders - Hitt, Michael A.; Harrison, Jeffrey S.; Ireland, R. Duane (Oxford ; New York : Oxford University Press, 2001)
This book gives a practical roadmap for making the most of the merger and acquisition opportunities, while avoiding the major pitfalls.
Includes bibliographical references (p. [189]-218) and index.
gau 18/06/14
Loans
Keywords: Consolidation and merger of corporations; Mergers and acquisitions